Standard specifications for transportation materials and methods of sampling and testing and provisional standards (American Association of State Highway and Transportation Officials, 2020)
"The AASHTO Materials Standards contain specifications, test methods, and provisional standards commonly used in the construction of highway facilities. The Materials Standards are updated three times per year, in mid-April, mid-June, and at the end of July. The April Update revises the sections on Hydraulic Cement and Lime, Fresh Concrete, Hardened Concrete, Pavement Measurement, Bridge and Pavement Preservation, and Quality Assurance and Environmental. The June Update revises the sections on General Manufactured Materials, including Concrete Drainage Structures, Flexible and Metallic Pipe, Markings and Coatings, and Safety Devices. The July Update revises the sections on Geotechnical, and Bituminous Materials and Mixtures."--Publication website